The Application of Generative AI in English Learning: Opportunities, Ethical Risks and Standardization Paths - Li, Daohan; Wang, Kexiang (Journal of Educational Research and Policies, 2026)
Driven by the digital wave, generative artificial intelligence (Generative AI), as a cutting-edge branch in the field of artificial intelligence, has brought revolutionary changes to English learning with its powerful capabilities in content generation, natural language interaction and intelligent analysis, effectively addressing many dilemmas in traditional English learning. Based on the technical characteristics of generative AI and combined with the essential needs of English learning, this paper systematically sorts out its application opportunities in personalized learning guidance, learning resource supply, immersive interactive scenario construction and learning efficiency improvement; deeply analyzes the potential ethical risks in its application process, including academic misconduct, excessive technological dependence, privacy disclosure and uneven quality of generated content; and puts forward targeted standardization paths from four subjects: learners, educators, technology providers and educational management departments. The purpose is to promote the in-depth integration of generative AI and English learning, realize the organic unity of technological innovation and educational ethics, and provide theoretical support and practical reference for the healthy and orderly application of generative AI in English learning.